Evaluation of Implementation Policy on Management of School Operational Fund (BOS) 2019 with Edward III Model - Rokhadiyati, Ary (Jurnal Pendidikan dan Pengajaran, 2020)
This study aims to evaluate the management of the School Operational Assistance (BOS) year 2019 at the Department of Education Culture Youth and Sport Semarang Regency. This is an evaluation research. Data were collected using documents study techniques, observation, and in-depth interviews. Data are validated by source and triangulation techniques. This study uses mixed method to get the whole pictures of the informant sources. What new about this research is that the data analysis technique uses the Edward III Model that looks at the factors of communication, resources, disposition and bureaucratic structure. The result of this study shows that implementation of School Operational Assistance (BOS) year 2019 is carried out in accordance with guidelines made by the government. The four aspects are all in very good categories. For communication aspect is in very good category because it gets 10 out of 12 points or 83 %. For Resources aspect is in very good category as well for its score is 16 out of 20 points or 80%. While for Disposition aspect is in very good category because it gets 17 out of 20 points or 85%. For the last aspect which is bureaucratic structure gets the highest points as it gets 8 out of 8 points or 100 %. Although the results are all very good, it still needs a little improvement on communication aspect especially on consistency factor since the guidelines has been revised for three times. Resources aspect on human resources quantity in BOS management team for there is only two persons managing 601 schools in Semarang Regency and also on disposition aspect because there is no incentive and award for the BOS management team. These results bring implication that the Department of Education in Semarang Regency can make improvement on the aspects which do not get maximal score and the for others Education Department in other Regencies or cities can learn from this research to manage BOS in better ways.